Frederick Field's Prolegomena to Origenis Hexaplorum Quae Supersunt, Sive Veterum Interpretum Graecorum in Totum Vetus Testamentum Fragmenta. Translated and annotated by Gerard J. Norton, OP with the collaboration of Carmen Hardin - Elliott, J. K. (The journal of theological studies, 2007)
Whereas many areas of study covered by the reviews in this journal are often reploughings of well-tilled fields, Septuagint studies still require much primary research, especially into the varying textual forms of the LXX. One such desideratum is the development of research into Origen's Hexapla. This inevitably must build on Field's often pioneering work published in 1875. (He was the first to see Homeric influence on Aquila, for example.) There is in place a Hexapla Institute Project; one of the more active of the members of its working group is Gerard Norton (whose name is misspelled on the cover and title page of the book under review here).